2019
DOI: 10.3390/nu11102453
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms of Probiotics Action in the Prevention and Treatment of Colorectal Cancer

Abstract: Colorectal cancer is one of the most common and most diagnosed cancers in the world. There are many predisposing factors, for example, genetic predisposition, smoking, or a diet rich in red, processed meat and poor in vegetables and fruits. Probiotics may be helpful in the prevention of cancer and may provide support during treatment. The main aim of this study is to characterize the potential mechanisms of action of probiotics, in particular the prevention and treatment of colorectal cancer. Probiotics’ poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(73 citation statements)
references
References 75 publications
(123 reference statements)
0
71
0
2
Order By: Relevance
“…species, only in SCA/P stools samples, which are suspected to be associated with CRC development [45] stimulating exaggerated immune responses via Th17 cells [46], as for other gastrointestinal cancers and other pathologies [46][47][48][49][50][51]. Considering such patterns and literature data demonstrating the ability of natural products and probiotics to modulate the immune system [52][53][54][55][56], a lot of studies are currently aimed at evaluating the effectiveness of them for the prevention of intestinal cancer [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…species, only in SCA/P stools samples, which are suspected to be associated with CRC development [45] stimulating exaggerated immune responses via Th17 cells [46], as for other gastrointestinal cancers and other pathologies [46][47][48][49][50][51]. Considering such patterns and literature data demonstrating the ability of natural products and probiotics to modulate the immune system [52][53][54][55][56], a lot of studies are currently aimed at evaluating the effectiveness of them for the prevention of intestinal cancer [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenic strain of Escherichia coli can synthesize several toxins, for example, cytotoxic necrotizing agent (CNF), cytolethal distending toxins (CDT), and other various virulence factors. Streptococcus gallolyticus and Enterococcus faecalis can also be connected to colorectal cancer [72,73].…”
Section: Modification Of the Intestinal Microbiota Compositionmentioning
confidence: 99%
“…In vitro and animal studies reported positive outcomes and protective anticancer effects of probiotics in CRC. 260,261 Bassaganya-Riera et al 260 evaluated the role of VSL#3 in modulating mucosal immune responses using mouse models of inflammation driven CRC. It was found that both adenoma and adenocarcinoma formation was diminished upon treatment.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%